Translating the WHA resolution in a member state: towards a German programme on 'Destigmatization' for individuals with visible chronic skin diseases. (8th July 2019) - Augustin, M.; Mrowietz, U.; Luck‐Sikorski, C.; von Kiedrowski, R.; Schlette, S.; Radtke, M.A.; John, S.M.; Zink, A.; Suthakharan, N.; Sommer, R.; ,
Abstract: Background: Even today, a substantial number of individuals with visible skin diseases still suffer from incomprehension and stigmatization. About 10 million people are affected by such diseases in Germany. The WHO strongly urges member states to take measures against stigmatization in skin diseases. Objectives: Objectives are the development of an action programme to raise awareness and address stigmatization. Therefore, conception, development and testing of interventions for the destigmatization of persons with skin diseases in Germany will be carried out. Methods: A series of actions addressing decision makers, politicians and the Federal Ministry of Health were initiated, all based on the World Health Assembly (WHA). Argumentation was largely based on data from health services research. Supported by the Federal Ministry of Health, a concept against stigmatization was developed by an expert consortium of researchers, dermatologists and patients. Specific strategies of structured destigmatization between those affected and those not will be developed and scientifically evaluated. Results: The activities addressed to politics were – to a large extent – successfully and financially supported by a 3‐year programme (2018–2020), designed to develop interventions against stigma. It was funded by the Federal Ministry of Health. The project includes conception and development, intervention and evaluation, data analyses and development of a long‐term concept. Conclusions: The WHO's call against stigmatization in psoriasis (resolution WHA67.9 and global report on psoriasis 2016) was taken into account and developed into a destigmatization programme supported by the German government and German politicians. This has been achieved by successful collaborations between dermatologists, researchers, patients and policymakers. Next step will be the testing of interventions in situations and surroundings, where stigmatization usually occurs. The data will be used for the implementation of a long‐term concept that can be used to continue destigmatization in Germany far beyond the project′s initial phase.